Farmers’ Management Practices of Potato Bacterial Wilt and Its Implications in Disease Prevalence in Kenya - Samuel Musah; Rael Birithia; Hellen Kamiri; Esther Kahariri (Journal of Agricultural Extension)
The widespread occurrence of potato bacterial wilt significantly contributes to the reduced potato yields in Kenya. Implementing effective management strategies for this disease usually necessitates understanding the knowledge and practices of farmers regarding potato bacterial wilt. To gain insights into farmers' knowledge and practices in managing bacterial wilt and to outline feasible intervention strategies, a survey was conducted involving 136 randomly selected farmers from four key potato-growing counties in Kenya between April and June 2019. The results indicate that farmers mainly identified potato bacterial wilt through visual indicators like plant wilting (53.7%) and tuber rot (30.9%). It was also noted that 59.6% of farmers believed the disease to be seed-borne, however, only 5.9% used certified seeds and 35.3% left rotting tubers in the field. This suggests a gap in farmers' understanding of the link between infection and disease control. Potato breeders should consider marketability traits alongside pest and disease resistance when developing new varieties. Education on diagnosis, epidemiology, and management of bacterial wilt is also needed.